2022
DOI: 10.1002/ppul.26052
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tests and subtypes of dysfunctional breathing in children with unexplained exertional dyspnea

Abstract: Background: Inappropriate hyperventilation during exercise may be a specific subtype of dysfunctional breathing (DB). Objective: To assess whether Nijmegen questionnaire and hyperventilation provocation test (HVPT) are able to differentiate inappropriate hyperventilation from other DB subtypes in children with unexplained exertional dyspnea, and normal spirometry and echocardiography. Methods: The results were compared between a subgroup of 25 children with inappropriate hyperventilation (increased V'E/V'CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The NQ 3 is a 16‐item questionnaire developed to detect hyperventilation and intended as a measurement of “functional respiratory complaints.” 6 , 10 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NQ 3 is a 16‐item questionnaire developed to detect hyperventilation and intended as a measurement of “functional respiratory complaints.” 6 , 10 …”
Section: Methodsmentioning
confidence: 99%
“… 8 , 12 A recent study found a positive correlation both between NQ and dyspnea during a cardiopulmonary exercise test, and between NQ and anxiety score in children with suspected DB. 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In cases where extubation or decannulation are prolonged because of anxiety, dysfunctional breathing (changes in breathing in the absence or in excess of medical pathology) often warrants specific treatment. 2 Mirtazapine, a noradrenergic and specific serotonergic (5HT)-ergic antidepressant, is associated with enhancement of 5HT-ergic and noradrenergic systems in the central nervous system. The noradrenergic effect is attributed to the blockade of inhibitory presynaptic α (α)2-autoreceptors.…”
Section: A Case Of Acute Conditioned Dyspnea During Tracheostomy Wean...mentioning
confidence: 99%
“…Protocol-based capping trials have led to readiness criteria with high specificity and a positive predictive value for successful decannulation 1 . In cases where extubation or decannulation are prolonged because of anxiety, dysfunctional breathing (changes in breathing in the absence or in excess of medical pathology) often warrants specific treatment 2 …”
mentioning
confidence: 99%